Shared transcriptional profiles of atypical B cells suggest common drivers of expansion and function in malaria, HIV, and autoimmunity - Holla, Prasida (Sci Adv, 2021)
Chronic infectious diseases have a substantial impact on the human B cell compartment including a notable expansion of B cells here termed atypical B cells (ABCs). Using unbiased single-cell RNA sequencing (scRNA-seq), we uncovered and characterized heterogeneities in naïve B cell, classical memory B cells, and ABC subsets. We showed remarkably similar transcriptional profiles for ABC clusters in malaria, HIV, and autoimmune diseases and demonstrated that interferon-γ drove the expansion of ABCs in malaria. These observations suggest that ABCs represent a separate B cell lineage with a common inducer that further diversifies and acquires disease-specific characteristics and functions. In malaria, we identified ABC subsets based on isotype expression that differed in expansion in African children and in B cell receptor repertoire characteristics. Of particular interest, IgD(+)IgM(lo) and IgD(−)IgG(+) ABCs acquired a high antigen affinity threshold for activation, suggesting that ABCs may limit autoimmune responses to low-affinity self-antigens in chronic malaria.